PERANCANGAN PROTOTIPE BIOREAKTOR UNTUK PENGOLAHAN LANJUT LIMBAH CAIR PABRIK KELAPA SAWIT (LCPKS) SECARA AEROBIK - Bambang Trisakti, Jhon Almer S. Pasaribu, Tri Afrianty, T. Husaini, Irvan (Jurnal Teknik Kimia USU, 2013)
LCPKS further processing is usually done by using activated sludge system is implemented in an open pond.This system requires a large enough dissolved oxygen so that if the system would lead to poor aeration then the HRT will be great. In addition to the spread of foul smell due to the system being used is open. This study aims to produce a prototype bioreactor that can be used to replace the above processing system. Bioreactor tank made ​​of transparent plastic tube that comes by baffles and stirrer are made ​​of stainless steel. In addition, the bioreactor is also equipped with a motor stirrer, aeration systems, and deodorizing unit. The resulting prototype has 11.078 cm high and 21.4 cm diameter, 9.2-liter operating volume, and fluid and baffle height is 24.5 cm. Bioreactor equipped with two stirrer blade that is horizontal turbine disc type at  7.13 cm of the tank bottom and paddle 4-rowing at 12.84 cm above the first blade. Bioreactor prototype has passed the leakage testand if the air flowing in at a constant velocity 0.5 m/s then the value of gasholdup (ε) is 0.02. Used this prototype for further processing LCPKS cause COD value of waste fell from 4,482 mg/l to 3,096 mg/l for 30 days long processed.